2002
DOI: 10.1038/sj.ijir.3900854
|View full text |Cite
|
Sign up to set email alerts
|

Significant decrease of the International Index of Erectile Function in male renal failure patients treated with hemodialysis

Abstract: In order to evaluate the erectile function in male renal failure patients treated with hemodialysis (HD), we investigated the International Index of Erectile Function (IIEF) in patients and healthy controls. The subjects were 174 male patients treated with HD, of whom 43 had diabetes mellitus (DM) and the remaining 131 patients did not have DM. The controls were 1133 healthy males. We evaluated the prevalence of erectile dysfunction (ED) using the erectile function (EF) score, which is one of the five domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 10 publications
8
43
3
Order By: Relevance
“…An overall erectile dysfunction prevalence of 86.5% on the basis of the erectile function domain of the IIEF was obtained; 32.5% had severe erectile dysfunction (erectile function domain score 0-10), out of which 52% were in the age range of 46-65 years, whereas only 13% were below 30 years of age. Moderate dysfunction (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) was present in 21.9% of the respondents, whereas 32.3% had mild dysfunction (22)(23)(24)(25). The severity of erectile dysfunction, however, increased with the patients' age.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…An overall erectile dysfunction prevalence of 86.5% on the basis of the erectile function domain of the IIEF was obtained; 32.5% had severe erectile dysfunction (erectile function domain score 0-10), out of which 52% were in the age range of 46-65 years, whereas only 13% were below 30 years of age. Moderate dysfunction (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) was present in 21.9% of the respondents, whereas 32.3% had mild dysfunction (22)(23)(24)(25). The severity of erectile dysfunction, however, increased with the patients' age.…”
Section: Resultsmentioning
confidence: 77%
“…2,3,10,14 Its etiology is multi-factorial, ranging from disease entities such as hypertension, 6,9 diabetes 15 and depression 8 to drugs used in the treatment of various conditions such as antihypertensives 16,17 and antipsychotics. 16 In this study, we found a prevalence rate of 86.5%.…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to increased aromatization of androgens to estrogens, higher SHBG levels (which reduce free testosterone), and possibly to an associated primary testicular failure. ED has been attributed to similar mechanisms in chronic renal failure, 15 and, owing to a defect of metabolic clearance of this hormone, may be associated with moderate hyperprolactinemia.…”
Section: Hyperprolactinemiamentioning
confidence: 99%
“…[20][21][22][23][24] Sexual dysfunction data for Asian populations are scant and primarily clinic-based. [25][26][27][28][29][30] Moreover, little is known about the prevailing attitudes and perceptions of sexual problems (SP) or its effects on QOL in Asian populations. Few large-scale, population-based studies on SP have been reported in Chinese population study.…”
Section: Introductionmentioning
confidence: 99%